Communicating financial reporting across continents - Mourier, Lise (HERMES - Journal of Language and Communication in Business, 2004)
Financial reporting is an area with distinctive terminology characteristics. High quality translations require both language and specialist knowledge. The varieties of English complicate the choice of language: British, American or international English? The article examines the challenges translators face when choosing between these ‘Englishes’. To determine how/whether a theoretical approach and a proper translation process can result in higher quality, the article will look at translation tools and strategies, problem-solving activities and consistency in choice of terminology.